Can cash transfer programs work in resource-poor countries?: the experience of Mozambique - Low, Jan W.; Garrett, James L.; Ginja, Vitória (International Food Policy Research Institute, 1999)
Cash transfer programs are rare in Sub-Saharan Africa. This paper describes the evolution of a cash transfer program in major urban centers of Mozambique, from its inception in 1990 through two major reorganizations until October 1998. Appropriate design, strong multisectoral political support and adequate administrative capacity are critical factors determining the success of such programs. Key lessons applicable to other resource-poor countries designing social assistance programs are drawn, recommending adequate targeted support to truly destitute persons incapable of physical labor in urban areas where administrative costs are more manageable than in more isolated rural sites.